2020
DOI: 10.1002/ldr.3686
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐offs between forage crop productivity and soil nutrients for different ages of alfalfa grassland

Abstract: Obtaining sustainable high yield and suitable soil nutrient management is crucial for cultivate alfalfa grassland. However, the information on the trade-offs between soil nutrient and productivity of alfalfa grassland following long-term cultivation under intensive agricultural management is scare. Six alfalfa grasslands of different ages under a highly intensive agricultural management system were chosen for this study.It was shown that long-term planting of alfalfa reduced soil nutrients overall. In the 0-10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…In Minnesota, the forage yield increased from the first to the second production year in all treatments, but much more for the intercropped systems (T3 and T4). In this study, the third production year was not evaluated, but literature indicates that alfalfa forage yield potential decreases as the plant ages after the third or fourth year [37,38].…”
Section: Alfalfa Forage Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…In Minnesota, the forage yield increased from the first to the second production year in all treatments, but much more for the intercropped systems (T3 and T4). In this study, the third production year was not evaluated, but literature indicates that alfalfa forage yield potential decreases as the plant ages after the third or fourth year [37,38].…”
Section: Alfalfa Forage Yieldmentioning
confidence: 99%
“…In summary, establishing alfalfa in intercropping with corn for grain is feasible and has multiple benefits to soil health and the environment in comparison with corn monoculture, as demonstrated by several pieces of research [14,15,19,30,32,37,48]. It has been demonstrated that alfalfa-silage corn intercropping systems have a higher total net revenue than corn monocultures, despite the yield penalty to corn in the seeding year [14,15,30].…”
Section: Alfalfa Forage Nutritive Valuementioning
confidence: 99%
“…Sown pasture is becoming a very important forage source for livestock production in China, which could relieve the pressure of natural grassland to maintain its sustainable development [ 1 , 2 , 3 ]. With the intensification of grassland and livestock production, the construction and utilization of high-yield and high-quality sown pasture become one of the important symbols of the modernization of grassland husbandry [ 4 , 5 ]. The ratio of sown pasture’s areas to rangeland’s areas in developed countries is generally above 0.1:1, such as 3.57:1 in New Zealand, 1.35:1 in United Kingdom and 0.58:1 in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen (N) fertilizer is applied more widely than phosphorus (P) and potassium (K) fertilizers. Many studies have been conducted on the contributions of fertilizer application to alfalfa yield and quality ( Undersander et al., 2011 ; Macolino et al., 2013 ; Fang et al., 2021 ). However, due to differences in cultivars, soils and climate conditions, the results show large variations or even opposite results.…”
Section: Introductionmentioning
confidence: 99%